Hydatothrips and Neohydatothrips (Thysanoptera, Thripidae) of East and South Asia with three new species from Taiwan - Wang, Chin-Ling (Zootaxa, 2007)
The tribe Sericothripini is divided into three genera, Sericothrips Haliday, Hydatothrips Karny and Neohydatothrips John. The genera Corcithrips Bhatti, Faureana Bhatti, Pyrothrips Bhatti, Sariathrips Bhatti and Zonothrips Priesner are considered new synonyms of Hydatothrips. The genera Elbuthrips Bhatti and Kazinothrips Bhatti are considered new synonyms of Neohydatothrips. Keys to the 23 species of Hydatothrips and 16 species of Neohydatothrips in East and South Asia, including Taiwan, China, Korea, Japan, India, Malaysia and the neighboring areas are given. Neohydatothrips pectinarius Kudo is a new synonym of N. medius Wang, N. populi Han is new synonym of N. elaeagni Kudo, and Z. luridus Ananthakrishnan is a new synonym of N. plynopygus (Karny). This paper describes three new species from Taiwan, H. flavidus, H. meriposa, and N. surrufus, and records from Taiwan for the first time the following four species: N. gracilipes Hood, N. plynopygus (Karny), N. samayunkur Kudo and N. tabulifer (Priesner).